2019
DOI: 10.1128/jb.00774-18
|View full text |Cite
|
Sign up to set email alerts
|

Pathoadaptive Alteration of Salmonella Biofilm Formation in Response to the Gallbladder Environment

Abstract: Typhoid fever, a human-specific disease, is primarily caused by the pathogen Salmonella enterica serovar Typhi. It is estimated that 3 to 5% of people infected with typhoid fever become chronic carriers. Studies have demonstrated that a mechanism of chronic carriage involves biofilm formation on gallstone surfaces. In the course of a previous study using a chronic carriage mouse model, a Salmonella enterica serovar Typhimurium isolate was recovered from a mouse gallstone that exhibited a 2-fold increase in bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
(43 reference statements)
0
15
0
1
Order By: Relevance
“…Typhi can form biofilms on human gallstones [57,58], a process which has been simulated with S . Typhimurium in a mouse model of chronic carriage; however, the nature of the extracellular matrix in such biofilms is still under investigation [37,59,60]. Our analysis highlighted the presence 4 premature stop codons in the bcsC of the S .…”
Section: Discussionmentioning
confidence: 88%
“…Typhi can form biofilms on human gallstones [57,58], a process which has been simulated with S . Typhimurium in a mouse model of chronic carriage; however, the nature of the extracellular matrix in such biofilms is still under investigation [37,59,60]. Our analysis highlighted the presence 4 premature stop codons in the bcsC of the S .…”
Section: Discussionmentioning
confidence: 88%
“…Antibiotics 2020, 9,59 6 of 27 the chronic gall bladder infection. The host immune response changes from an early proinflammatory response to a later anti-inflammatory response [76] whereas S. Typhi adapts to the gall bladder environment by increasing the biofilm forming ability and the capacity for persistence and simultaneously reducing the ability to cause acute infections [77,78]. It has also been shown that S. Paratyphi A can persist in the gallbladder [79] and accumulating evidence indicate a role for nontyphoidal Salmonellae in persistent infections.…”
Section: Recalcitrant Typhoid Fever and Predisposition To Hepatobiliamentioning
confidence: 99%
“…Although the majority of bacteria ingested are killed by stomach acid, bile or intestinal defensins, if the dose is high enough (only about 1000–10,000 colony forming units) surviving Salmonella can colonize the gut lumen or even invade the mucosa and proliferate within epithelial cells [ 148 ]. Importantly, from the intestine passing through the liver Salmonella can enter the gallbladder [ 149 , 150 ].…”
Section: The Enteric Pathogens: Campylobacter Jejuni mentioning
confidence: 99%